2018
DOI: 10.1111/jth.14280
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structural and mechanical effects of procoagulant agents on neonatal fibrin networks following cardiopulmonary bypass

Abstract: To cite this article: Nellenbach K, Guzzetta NA, Brown AC. Analysis of the structural and mechanical effects of procoagulant agents on neonatal fibrin networks following cardiopulmonary bypass. J Thromb Haemost 2018; 16: 2159-67. Essentials• The standard of care (SOC) for treating neonatal bleeding is transfusion of adult blood products. • We compared neonatal clots formed with cryoprecipitate (SOC) to two procoagulant therapies. • The current SOC resulted in clots with increased stiffness and decreased fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…These structural characteristics in neonatal clotting were also associated with clot function, such as increased clot degradation post-CPB, and mechanical properties, such as decreased clot stiffness post-CPB. 15,16 These studies also revealed that clot structure of baseline neonatal clots differed significantly from adult clot properties. Neonatal clots were found to have more highly aligned fibers and more porous clot structures than adult clots.…”
Section: Clot Structure and Clinical Outcomes Structural Clot Changesmentioning
confidence: 88%
See 2 more Smart Citations
“…These structural characteristics in neonatal clotting were also associated with clot function, such as increased clot degradation post-CPB, and mechanical properties, such as decreased clot stiffness post-CPB. 15,16 These studies also revealed that clot structure of baseline neonatal clots differed significantly from adult clot properties. Neonatal clots were found to have more highly aligned fibers and more porous clot structures than adult clots.…”
Section: Clot Structure and Clinical Outcomes Structural Clot Changesmentioning
confidence: 88%
“…Clinical outcomes associated with bleeding risks have been examined through direct clot structure analysis. 15 In recent studies using plasma samples collected from neonates younger than 30 days undergoing cardiopulmonary bypass (CPB), analysis of clot structure has provided new information regarding bleeding phenotypes often observed in these patients. The hemostatic system is immature for the first year of life and in neonates, bleeding is a critical issue especially after CPB.…”
Section: Clot Structure and Clinical Outcomes Structural Clot Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15,16 Also, our previous studies demonstrate that the ex vivo addition of procoagulant therapies to post-CPB plasma from human neonates enhances fibrin clot properties. [17][18][19][20] We hypothesize that the in vitro addition of these hemostatic therapies to neonatal porcine samples will similarly augment plasma fibrin clot properties. If confirmed, piglets could serve as a suitable and much needed preclinical model for evaluating neonatal specific hemostatic therapies.…”
Section: What This Article Tells Us That Is Newmentioning
confidence: 99%
“…Assuming that thrombin generation is decreased significantly post-CPB (and that remains to be proven), 16 the effect of rFVIIa administration on thrombin generation, clot formation, and hemostasis at the local site of injury rather than systemically remains to be determined. Although data obtained from ex vivo studies suggest that rFVIIa and/or activated prothrombin complex concentrates can be used to augment thrombin generation 17 and enhance the neonatal fibrin network, 18 in vivo studies are urgently needed to understand the effect of those procoagulant agents on local and systemic clot formation. Assuming that rFVIIa effectively improves in vivo hemostasis, adequate concentrations of platelets and fibrinogen should be present before its administration is considered.…”
mentioning
confidence: 99%